PDGF-BB overexpressing dental pulp stem cells improve angiogenesis in dental pulp regeneration - Jiang, Wentao; Duan, Shuhan; Li, Weiping; Yan, Huijiao; Si, Chenli; Xu, Ningwei; Li, Yishuai; Zhang, Wenjie; Gu, Shensheng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAngiogenesis represents a critical challenge in dental pulp regeneration due to the tissue’s restricted nutrient supply through a 0.5-mm apical foramen. While dental pulp stem cells (DPSCs) hold regenerative potential, their limited vascularization capacity impedes clinical applications. Through Single-cell RNA sequencing (scRNA-seq) analysis of human dental pulp, we discovered a PDGF (+) mesenchymal subset exhibiting enhanced angiogenic signatures, suggesting targeted cell selection could overcome this bottleneck.MethodsScRNA-seq identified PDGF (+) subpopulation in human pulp samples, validated through multiplex immunohistochemical of the localization of PDGF/CD73/CD31. PDGF-BB-overexpressing DPSCs were engineered via lentiviral vectors. Functional assessments included: 1) CCK-8/Edu/cell cycle/transwell assays for proliferation and migration ability 2) HUVECs co-culture models analyzing chemotaxis and tube formation 3) Vascularized tissue formation in rat kidney capsule transplants.Results and DiscussionThe CD73 (+) PDGF (+) subpopulation demonstrated spatial correlation with CD31 (+) vasculature. PDGF-BB overexpression enhanced DPSCs' proliferative capacity and migration capacity. Co-cultured HUVECs exhibited increased tube formation with PDGF-BB group. In vivo transplants generated more vascular structures containing CD31 (+) endothelia. These findings establish PDGF-BB engineering as an effective strategy to amplify DPSCs' angiogenic potential, while emphasizing the therapeutic value of functionally-defined stem cell subpopulations in pulp regeneration.